Preaching and performance: Theo-dramatic paradoxes in a South African sermon - Nell, Ian A (Stellenbosch Theological Journal, 2017)
Preaching and performance is a relatively recent development in homiletical discourses and preaching practices. There is much promise in approaching preaching in this creative way. Attention will be paid to different promises related to this homiletical approach. In a next round of reflection the attention shifts to the way in which a specific approach to performance, also known as theo-drama, can not only enhance the preaching act, but also helps to understand the paradoxical role of the preacher, the audience and even God in the preaching event. This will be illustrated by looking at one of the sermons of John de Gruchy, which he preached in a very specific time in the history of South Africa. Attention will also be given to the way in which he performed a prophetic and therefore paradoxical role in his opposition to the apartheid government.